The Differential Role of Smell and Taste For Eating Behavior. (March 2017) - Boesveldt, Sanne; de Graaf, Kees
Food choice and food intake are guided by both sensory and metabolic processes. The senses of taste and smell play a key role in the sensory effects on choice and intake. This article provides a comprehensive overview of, and will argue for, the differential role of smell and taste for eating behavior by focusing on appetite, choice, intake, and satiation. The sense of smell mainly plays a priming role in eating behavior. It has been demonstrated that (orthonasal) odor exposure induces appetite specifically for the cued food. However, the influence of odors on food choice and intake is less clear, and may also depend on awareness or intensity of the odors, or personality traits of the participants. Taste on the other hand, has a clear role as a (macro)nutrient sensing system, during consumption. Together with texture, taste is responsible for eating rate, and thus in determining the oral exposure duration of food in the mouth, thereby contributing to satiation. Results from these experimental studies should be taken to real-life situations, to assess longer-term effects on energy intake. With this knowledge, it will be possible to steer people's eating behavior, as well as food product development, toward a less obesogenic society.